Analisis Ujaran Kebencian Terhadap Kiki Saputri Di Media Sosial Twitter - Shada Fadhilah Ginting; Siti Hadijah; Siti Hasanah Nasution; Frinawaty Lestarina Barus (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Social media is used by people from various groups to communicate and become a forum for conveying their ideas and thoughts about this information. Communicating on social media can have negative impacts that are detrimental to certain people or certain parties, such as defamation of someone's good name and hate speech. This research aims to describe the form and meaning of hate speech against comic Kiki Saputri on Twitter social media. This research uses a qualitative descriptive method. Data collection was obtained from screenshots of the owners of these tweets which were uploaded and spread across various social media pages. From this research, there is data on hate speech from netizens' tweets typed via Kiki Saputri's Twitter social media comments. This research concluded that there were seven speech acts containing hate speech towards Kiki Saputri found in this research, namely insulting hate speech. Most of the tweets on Twitter are insulting and express annoyance, expressing dislike, criticizing, cursing, using harsh words and speech expressing dislike and annoyance with the subject of discussion.